EFEKTIVITAS EKSTRAK DAUN KAYU MANIS (Cinnamomum burmanni Blume) DALAM MENEKAN PERTUMBUHAN JAMUR Colletotrichum magnum Rossman & Allen PENYEBAB PENYAKIT ANTRAKNOSA PADA PEPAYA (Carica papaya Linnaeus) - Fitriyah, Wafiatul; Sudirga, Sang Ketut; Gari, Ni Made (SIMBIOSIS; Vol 11 No 1 (2023)DO - 10.24843/JSIMBIOSIS.2023.v11.i01.p09, 2023)
Anthracnose is a disease which is often found attacking plants. This disease can cause dieback or leaf tip damage of mature plants then followed by infection in the fruits, Consequently, this can result in the decrease of productivity. One of the causes of anthracnose is the pathogenic fungus Colletotrichum magnum . This fungus can infect several cultivated plants, one of which is papaya plants. This study aimed to determine the effectiveness of cinnamon leaf extract ( Cinnamomum burmanni . Blume) in suppressing the growth of the fungus C. magnum and to analyze the class of compounds contained in cinnamon leaf extract. The method used in this study was a Completely Randomized Design (CRD) with 1 negative control, 1 positive control, and 5 treatments with concentrations of 1%, 2%, 3%, 4%, 5%, each treatment was repeated 4 times and then tested phytochemical screening. The results of the invitro study showed that cinnamon leaf extract was able to inhibit the growth of C. magnum as seen from the MIC test results, namely a concentration of 0.6% with an inhibition zone diameter of 8.37 mm. The results showed that as the concentration of cinnamon leaf extract increased, the diameter of the inhibition zone obtained was getting bigger. what you get is bigger. The concentration of 5% that has the largest inhibition zone among the concentration treatments, which is 19.77 mm. The results of phytochemical screening on cinnamon leaf extract showed that the cinnamon leaf extract contains positive groups of alkaloids, steroids, phenolic compounds, saponins, flavonoids, and tannins. Keyword: anthracnose, Cinnamon leaves, Inhibition, Colletotrichum magnum.